Bank Regulation and Sovereign Risk: A Paradox - António Afonso; André Teixeira (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates the impact of banking prudential regulation on sovereign risk. We show that prudential regulation reduces sovereign risk and induces governments to spend more. As a result, countries with tight prudential regulation have lower primary budget balances and accumulate more government debt over time. We find that prudential regulation reduces private debt, while paradoxically increasing government debt. We explore several explanations for this paradox. Our results suggest that prudential regulation enables governments to accumulate debt because they improve the nation's credit rating and its borrowing conditions in sovereign bond markets.
Keywords: E52; E58; E62; H30; G28; 330; banking regulation; fiscal policy; macroprudential policy; sovereign debt; sovereign risk